2015
DOI: 10.1097/jto.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Role of Comorbidity on Survival after Radiotherapy and Chemotherapy for Nonsurgically Treated Lung Cancer

Abstract: Comorbidity has a limited effect on survival and only for patients treated with chemotherapy. It is rather the performance of the patient at diagnosis than the medical history that prognosticates survival in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 21 publications
1
48
0
1
Order By: Relevance
“…Just as surgeons should be careful in operating on patients with medical comorbidities (8), radiation oncologists must be careful when selecting patients most likely to benefit from SABR (9). To our knowledge, currently no validated instrument exists to assist in determining the prognosis of ES-NSCLC patients treated with SABR (10), which would be useful in maximizing benefit to the broader community and minimizing undertreatment (11).…”
Section: Introductionmentioning
confidence: 97%
“…Just as surgeons should be careful in operating on patients with medical comorbidities (8), radiation oncologists must be careful when selecting patients most likely to benefit from SABR (9). To our knowledge, currently no validated instrument exists to assist in determining the prognosis of ES-NSCLC patients treated with SABR (10), which would be useful in maximizing benefit to the broader community and minimizing undertreatment (11).…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of co-morbidity was higher for patients > 70 years (69%) than for younger patients (52%) and was 8% higher for men than for women. More recently, the role of comorbidity for non-surgically treated lung cancer was studied in the Danish lung cancer registry [2]. Of the 20,548 patients, 50% had a least one comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients who underwent chemotherapy and radiotherapy for lung cancer, Charlson scores of >2 was only 8% for those <60 year old but increased to 26% and 43% for patients between 60- and 69 year old and 70- and 79-year old, respectively [12] . Other studies also showed an increase of prevalence and severity of comorbidity among elderly cancer patients using different indexes.…”
Section: Resultsmentioning
confidence: 96%